The Application of Kitchen Waste Changed the Community Structure and Composition of AOA and AOB by Affecting the pH and Soil Organic Carbon of Red Soil - Zhang, Donghui; Chen, Wen; Wen, Changtao; Hou, Zheng; Wang, Keqin; Song, Yali (Agronomy (Basel), 2024)
To investigate the effects of kitchen waste on the chemical properties of acidic red soil and the community structure of ammonia–oxidizing archaea (AOA) and ammonia–oxidizing bacteria (AOB), a study was conducted in the flue–cured tobacco farmland ecosystem of the Erlongtan small watershed in central Yunnan. Eight fertilization methods were applied: no fertilization control CK, single application of chemical fertilizer T1 (1 t·hm−2), kitchen waste combined with a chemical fertilizer (T2:12 t·hm−2 + 1 t·hm−2, T3:15 t·hm−2 + 1 t·hm−2, T4:18 t·hm−2 + 1 t·hm−2), and single application of kitchen waste (T5:12 t·hm−2, T6:15 t·hm−2, T7:18 t·hm−2). The numbers twelve, fifteen, and eighteen in brackets represent the amount of food waste applied, and one represents the amount of chemical fertilizer applied. The study evaluated the effects of kitchen waste on soil chemical properties, the community structure and composition of AOA and AOB, and the relationship between soil chemical properties and these microbial communities in acidic red soil. The results showed that: (1) single application of kitchen waste (T5, T6, T7) effectively improved soil nutrient status (SOC increased by 15.79–217.24%; TN increased by 1.53–92.99%; NH4+–N increased by 18.19–520.74%; NO3−–N) increased by 15.54–750.61%), and alleviated acidification. (2) Temporal variations had a more significant effect on the community structure of AOA and AOB than different treatments. The dominant phyla of AOA were Thaumarchaeota, Crenarchaeot. The dominant phylum of AOB was Proteobacteria, and the dominant genera were Nitrosospira and norank_Bacteri. (3) The number of AOA co–occurrence network nodes were equivalent to that of AOB, but AOB had more connection edges, indicating a more complex interaction network. In contrast, AOA exhibited higher modularity, reflecting tighter internal connections and greater stability. The AOA co–occurrence network showed stronger performance during the maturity and fallow stages, while AOB interactions were most active during the topping stage. (4) AOA demonstrated a strong correlation with soil chemical properties during the topping and maturity stages, whereas AOB showed a stronger correlation at the rosette and fallow stages. Among soil chemical factors, pH and SOC were identified as the primary drivers influencing AOA and AOB community abundance and structural differentiation. In conclusion, kitchen waste application enhances the nutrient content of acidic red soil and influences the niche differentiation of AOA and AOB, thereby affecting nitrogen recycling. This approach represents an environmentally friendly and sustainable fertilization method.